A composite positive electrode material and its preparation method and application
By doping rare earth elements and boron elements into the positive electrode material of solid lithium batteries, and covering the surface with sulfide solid electrolyte and other materials, the problem of reducing charge and discharge efficiency and capacity attenuation of solid lithium batteries in high/low temperature environments is solved, and the battery's good electrical performance and extended life in a wide temperature domain are achieved.
Patent Information
- Application Number
- CN202411794002.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Solid-state lithium batteries reduce charge and discharge efficiency and attenuate battery capacity in high/low temperature environments, affecting the battery's cycle performance and life.
A composite positive electrode material, including lithium iron phosphate as the basic raw material, is doped with rare earth elements and boron elements, and is coated with a mixture of sulfide solid electrolyte, conductive agent and lithium salt on its surface.
Through element doping and surface coating, the interface impedance is reduced, the layer spacing of materials is increased, the diffusion rate of lithium ions is improved, the electrical performance of the battery in a wide temperature range, and the service life of the battery is extended.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion battery materials, and specifically discloses a composite positive electrode material and a preparation method and application thereof. Background Art
[0002] The flammable, leaky and volatile properties of traditional liquid electrolytes at high temperatures make lithium-ion batteries a potential safety hazard under extreme conditions. The energy density of liquid lithium-ion batteries is close to its theoretical limit, making it difficult to meet the demand for higher energy density in future technologies. As an emerging battery technology, solid-state batteries have multiple advantages and have become one of the research hotspots of lithium-ion batteries. Solid-state batteries use solid electrolytes instead of liquid electrolytes, which can significantly improve the safety and stability of batteries. The use of solid electrolytes can also allow the use of lithium metal as a negative electrode material, thereby increasing the energy density of the battery. At the same time, solid electrolytes are non-flammable and have a lower risk of combustion and explosion, making batteries more reliable in extreme environments. In addition, solid electrolytes also have good high temperature resistance, can adapt to a wider operating temperature range, and enhance the stability and reliability of the battery. Therefore, solid-state batteries are considered to be one of the important development directions of future battery technology and have broad application prospects.
[0003] However, the ionic conductivity of solid-state lithium batteries is lower at low temperatures, resulting in a smaller output current and lower discharge performance at low temperatures. In addition, since the solid electrolyte and the electrode are in solid-solid contact, the effective contact area is small, and the interface impedance problem is more prominent at low temperatures, resulting in increased internal resistance of the battery, reduced charge and discharge efficiency, and intensified polarization. At high temperatures, the electrode material is prone to expansion, resulting in blockage or deformation of the ion transmission channel, increasing the ion transmission resistance and reducing the battery's charge and discharge efficiency. High temperatures will accelerate the side reactions inside the battery, causing battery capacity decay, affecting the battery's cycle performance and service life, and reducing safety.
[0004] Based on this, developing a solid-state lithium battery with stable performance over a wide temperature range has great practical significance for the application of lithium batteries in harsh environments. Summary of the invention
[0005] In view of the problem that solid-state lithium batteries in the prior art will have reduced charging and discharging efficiency and battery capacity attenuation under high / low temperature environments, which affects the battery's cycle performance and life, the present invention provides a composite positive electrode material and its preparation method and application. The composite positive electrode material includes a positive electrode active material and a coating material coated on the surface of the positive electrode active material. The present invention uses lithium iron phosphate as the basic raw material and prepares a positive electrode active material LiFe by doping rare earth elements and boron elements. x Mn y RE z B (1-x-y-z)PO4, wherein 0.1<x≤0.3, 0.1<y<0.3, 0.1<z<0.3, 0.1<1-xyz<0.2; and a layer of a mixture of sulfide solid electrolyte, conductive agent and lithium salt as raw materials is coated on the surface of the positive electrode active material. Element doping and surface coating effectively reduce the interface impedance, increase the interlayer spacing of the material, and improve the diffusion rate of lithium ions in this problem, so that the lithium-ion battery also has good electrical properties in a wide temperature range.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following specific technical solutions:
[0007] The first aspect of the present invention provides a composite positive electrode material, the composite positive electrode material comprising a positive electrode active material and a coating material coated on the surface of the positive electrode active material; wherein the positive electrode active material is LiFe x Mn y RE z B (1-x-y-z) PO4, wherein 0.1<x≤0.3, 0.1<y<0.3, 0.1<z<0.3, 0.1<1-xyz<0.2, and RE is any one of La, Ce, Nd, Y or Sm; and the coating material is a mixture of a sulfide solid electrolyte, a conductive agent and a lithium salt.
[0008] Compared with the prior art, the present invention first designs a positive electrode active material, and uses rare earth elements and non-metallic boron elements to co-dope lithium iron manganese phosphate, which effectively improves the stability and conductive efficiency of the positive electrode material in a high temperature environment or a low temperature environment. Among them, the doping of rare earth elements can not only expand the lithium ion diffusion channel, reduce the diffusion resistance of lithium ions, accelerate the diffusion rate of lithium ions at low temperatures, and improve the rate performance and low-temperature discharge capacity of the battery, but also improve and enhance the structural stability of the lithium iron manganese phosphate material, so that its cycle performance in a low temperature environment is better, reduce capacity decay, and extend the service life of the battery. In addition, rare earth elements can act as lattice stabilizers, which can inhibit the expansion and contraction of the lithium iron manganese phosphate lattice at high temperatures, maintain the stability of the crystal structure, thereby improving the cycle performance of the positive electrode material at high temperatures and reducing the capacity decay during the charge and discharge process. The introduction of boron elements can change the crystal structure of lithium iron manganese phosphate, reduce the diffusion activation energy of lithium ions, thereby increasing the migration rate of lithium ions in the material, and improving the rate performance and cycle performance of the battery.
[0009] The present invention also coats a layer of a mixture of a sulfide solid electrolyte, a conductive agent and a lithium salt on the surface of the positive electrode active material. The sulfide solid electrolyte itself has high ionic conductivity and can construct an efficient ion transmission channel inside the positive electrode material, accelerate the migration rate of lithium ions, and improve the battery charging and discharging efficiency. However, there is resistance between the sulfide solid electrolyte and the surface of the positive electrode active material. The addition of conductive carbon black can increase the surface conductivity of the positive electrode active material and cooperate with the sulfide solid electrolyte to improve the ion transmission efficiency. Lithium salt can provide more lithium ions, further enhance ionic conductivity, improve battery charging and discharging performance, and can also participate in the formation of a stable interface layer to optimize the interface performance between the positive electrode material and the electrolyte.
[0010] Preferably, the positive electrode active material is LiFe 0.29 Mn 0.25 Nd 0.28 B 0.18 PO4、LiFe 0.3 Mn 0.26 Sm 0.25 B 0.19 PO4 or LiFe 0.25 Mn 0.27 La 0.29 B 0.19 Any of PO4.
[0011] Preferably, the method for preparing the positive electrode active material comprises the following steps:
[0012] S1. Weigh a lithium source, an iron source, a manganese source, an RE source, a boron source and a phosphorus source according to the designed ratio, mix them, and perform ball milling to obtain a mixture;
[0013] S2. In an inert atmosphere, heating the mixture to 500° C.-600° C. for pre-sintering to obtain a primary sintered product;
[0014] S3. In an inert atmosphere, the primary sintered product is heated to 800° C.-900° C. again, calcined, cooled, and ground to obtain a positive electrode active material.
[0015] Further preferably, in S1, the lithium source is lithium oxide.
[0016] Further preferably, in S1, the iron source is iron oxide.
[0017] Further preferably, in S1, the manganese source is manganese dioxide.
[0018] Further preferably, in S1, the RE source is any one of lanthanum oxide, cerium oxide, neodymium oxide, yttrium oxide or samarium oxide.
[0019] Further preferably, in S1, the boron source is boric acid.
[0020] Further preferably, in S1, the phosphorus source is phosphorus pentoxide.
[0021] Further preferably, in S1, the ball-to-material ratio of the ball mill is 25:1-35:1, the rotation speed of the ball mill is 400rpm-500rpm, and the ball milling time is 3h-8h.
[0022] Further preferably, in S2, the temperature is raised to 500°C-600°C by programmed heating, and the heating rate is 2°C / min-10°C / min.
[0023] Further preferably, in S2, the pre-sintering time is 4h-6h.
[0024] Further preferably, in S3, the temperature is raised to 800°C-900°C by programmed heating, and the heating rate is 5°C / min-10°C / min.
[0025] Further preferably, in S3, the calcination time is 12h-16h.
[0026] Preferably, the coating material is a sulfide solid electrolyte, a conductive agent and a lithium salt in a mass ratio of 1:0.2:0.3-1:0.3:0.5.
[0027] Preferably, the coating thickness of the coating material is 3nm-10nm.
[0028] Preferably or further preferably, the sulfide solid electrolyte is Li2S-SiS2, Li2S-B2S3, Li6PS5Cl, Li7P3S 11 , LiSiPSCl, LiSiPSBr or LiSiPSI.
[0029] Preferably or further preferably, the particle size of the sulfide solid electrolyte satisfies the following conditions: 1 μm<Dv90<1.5 μm, 0.5 μm<Dv50<1.5 μm, 0.5 μm<Dv10<1 μm.
[0030] Preferably or further preferably, the conductive agent is conductive carbon black.
[0031] Preferably or further preferably, the lithium salt is any one or two of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(difluorosulfonyl)imide, lithium bis(oxalatoborate) or lithium difluorooxalatoborate.
[0032] The second aspect of the present invention provides a method for preparing the composite positive electrode material, comprising the following steps:
[0033] Step 1: weighing a sulfide solid electrolyte, a conductive agent and a lithium salt according to the designed ratio, and mixing them evenly to obtain a coating mixture;
[0034] Step 2: dispersing the coating mixture in an alcohol solvent, adding a positive electrode active material, ball milling and mixing, and drying to obtain a composite positive electrode material precursor;
[0035] Step 3: calcining the composite positive electrode material precursor at 400° C.-500° C. to obtain a composite positive electrode material.
[0036] Preferably, in step 2, the alcohol solvent is anhydrous methanol or anhydrous ethanol.
[0037] Preferably, in step 2, the mass volume ratio of the coating mixture to the alcohol solvent is 1 g:3 mL-1 g:5 mL.
[0038] Preferably, in step 2, the mass ratio of the coating mixture to the positive electrode active material is 1.2:1-2.0:1.
[0039] Preferably, in step 2, the rotation speed of the ball mill is 200 rpm-300 rpm, and the time of the ball mill is 3 h-4 h.
[0040] Preferably, in step three, the calcination time is 4h-6h.
[0041] The third aspect of the present invention provides the use of the composite positive electrode material or the composite positive electrode material prepared by the method for preparing the composite positive electrode material in a solid-state lithium battery.
[0042] In summary, the present invention designs a composite positive electrode material and its preparation method and application, wherein the composite positive electrode material includes a positive electrode active material and a coating material coated on the surface of the positive electrode active material, and lithium iron phosphate is used as the basic raw material, and a positive electrode active material is prepared by doping rare earth elements and boron elements, and a layer of a mixture of sulfide solid electrolyte, conductive agent and lithium salt as raw materials is coated on the surface of the positive electrode active material. The present invention effectively reduces the interface impedance, increases the interlayer spacing of the material, and improves the diffusion rate of lithium ions through element doping and surface coating, so that the solid-state lithium battery has good electrical properties in a wide temperature range. The technical solution of the present invention effectively solves the problem in the prior art that the solid-state lithium battery will have reduced charging and discharging efficiency and battery capacity attenuation under high / low temperature environments, which affects the cycle performance and life of the battery. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] This embodiment provides a composite positive electrode material and a preparation method thereof, which specifically includes the following contents:
[0046] The composite positive electrode material comprises a positive electrode active material and a coating material coated on the surface of the positive electrode active material; wherein the positive electrode active material is LiFe 0.29 Mn 0.25 Nd 0.28 B 0.18 PO4; the coating layer material is Li2S-SiS2, conductive carbon black and lithium hexafluorophosphate in a mass ratio of 1:0.2:0.4.
[0047] The method for preparing the composite positive electrode material comprises the following steps:
[0048] Step 1: weigh 10g Li2S-SiS2, 2g conductive carbon black and 4g lithium hexafluorophosphate according to the designed ratio, mix them evenly to obtain a coating mixture;
[0049] Step 2: Disperse the coating mixture in 50 mL of anhydrous methanol and add 10 g of LiFe 0.29 Mn 0.25 Nd 0.28 B 0.18 PO4, ball milling and mixing at a speed of 200 rpm for 4 h, and drying to obtain a composite cathode material precursor;
[0050] Step 3: calcining the composite positive electrode material precursor at 450° C. for 5 h to obtain a composite positive electrode material.
[0051] Wherein, the positive electrode active material LiFe 0.29 Mn 0.25 Nd 0.28 B 0.18 The preparation method of PO4 comprises the following steps:
[0052] S1. According to the designed ratio, 1.16 g lithium oxide, 1.84 g iron oxide, 0.88 g manganese dioxide, 3.78 g neodymium oxide, 0.44 g boric acid and 5.68 g phosphoric acid were weighed and mixed, and the mixture was put into a ball mill with a ball-to-material ratio of 30:1, and the mixture was ball-milled at a speed of 450 rpm for 6 h to obtain a mixture;
[0053] S2. In an inert atmosphere, the mixture is heated to 550° C. at a heating rate of 5° C. / min, and pre-sintered for 5 hours to obtain a primary sintered product;
[0054] S3. In an inert atmosphere, the primary sintered product is heated to 850° C. at a heating rate of 5° C. / min again, calcined for 14 h, cooled, and ground to obtain a positive electrode active material.
[0055] Wherein, the particle size of the sulfide solid electrolyte meets the following conditions: 1 μm<Dv90<1.5 μm, 0.5 μm<Dv50<1.5 μm, 0.5 μm<Dv10<1 μm.
[0056] Example 2
[0057] This embodiment provides a composite positive electrode material and a preparation method thereof, which specifically includes the following contents:
[0058] The composite positive electrode material comprises a positive electrode active material and a coating material coated on the surface of the positive electrode active material; wherein the positive electrode active material is LiFe 0.3 Mn 0.26 Sm 0.25 B 0.19 PO4; the coating layer material is Li2S-B2S3, conductive carbon black and lithium hexafluorophosphate in a mass ratio of 1:0.3:0.4.
[0059] The method for preparing the composite positive electrode material comprises the following steps:
[0060] Step 1: According to the designed ratio, 10 g Li2S-B2S3, 3 g conductive carbon black and 4 g lithium tetrafluoroborate were weighed and mixed evenly to obtain a coating mixture;
[0061] Step 2: Disperse the coating mixture in 50 mL of anhydrous methanol and add 10 g of LiFe 0.3 Mn 0.26 Sm 0.25 B 0.19 PO4, ball milling and mixing at a speed of 300 rpm for 3 h, and drying to obtain a composite cathode material precursor;
[0062] Step 3: calcining the composite positive electrode material precursor at 400° C. for 6 hours to obtain a composite positive electrode material.
[0063] Wherein, the positive electrode active material LiFe 0.3 Mn 0.26 Sm 0.25 B 0.19 The preparation method of PO4 comprises the following steps:
[0064] S1. According to the designed ratio, 1.16 g lithium oxide, 1.86 g iron oxide, 0.88 g manganese dioxide, 3.38 g samarium oxide, 0.45 g boric acid and 5.68 g phosphoric acid were weighed and mixed, and the mixture was put into a ball mill with a ball-to-material ratio of 35:1. The mixture was ball-milled at a speed of 450 rpm for 8 h to obtain a mixture.
[0065] S2. In an inert atmosphere, the mixture is heated to 500° C. at a heating rate of 5° C. / min, and pre-sintered for 5 hours to obtain a primary sintered product;
[0066] S3. In an inert atmosphere, the primary sintered product is heated to 850° C. at a heating rate of 10° C. / min again, calcined for 15 h, cooled, and ground to obtain a positive electrode active material.
[0067] Wherein, the particle size of the sulfide solid electrolyte meets the following conditions: 1 μm<Dv90<1.5 μm, 0.5 μm<Dv50<1.5 μm, 0.5 μm<Dv10<1 μm.
[0068] Example 3
[0069] This embodiment provides a composite positive electrode material and a preparation method thereof, which specifically includes the following contents:
[0070] The composite positive electrode material comprises a positive electrode active material and a coating material coated on the surface of the positive electrode active material; wherein the positive electrode active material is LiFe 0.25 Mn 0.27 La 0.29 B 0.19 PO4; the coating layer material is Li2S-SiS2, conductive carbon black and lithium hexafluorophosphate in a mass ratio of 1:0.2:0.5.
[0071] The method for preparing the composite positive electrode material comprises the following steps:
[0072] Step 1: weigh 10g Li2S-SiS2, 2g conductive carbon black and 5g lithium hexafluorophosphate according to the designed ratio, mix them evenly to obtain a coating mixture;
[0073] Step 2: Disperse the coating mixture in 50 mL of anhydrous methanol and add 10 g of LiFe 0.25 Mn 0.27 La 0.29 B 0.19 PO4, ball milling and mixing at a speed of 250 rpm for 4 h, and drying to obtain a composite cathode material precursor;
[0074] Step 3: calcining the composite positive electrode material precursor at 500° C. for 5 h to obtain a composite positive electrode material.
[0075] Wherein, the positive electrode active material LiFe 0.25 Mn 0.27 La 0.29 B 0.19 The preparation method of PO4 comprises the following steps:
[0076] S1. According to the designed ratio, 1.16 g lithium oxide, 1.54 g iron oxide, 0.91 g manganese dioxide, 3.67 g neodymium oxide, 0.45 g boric acid and 5.68 g phosphoric acid were weighed and mixed, and put into a ball mill, and the ball-to-material ratio was set to 25:1, and the ball milling was performed at a speed of 500 rpm for 4 h to obtain a mixture;
[0077] S2. In an inert atmosphere, the mixture is heated to 560° C. at a heating rate of 8° C. / min, and pre-sintered for 5 hours to obtain a primary sintered product;
[0078] S3. In an inert atmosphere, the primary sintered product is heated again to 800° C. at a heating rate of 8° C. / min, calcined for 16 h, cooled, and ground to obtain a positive electrode active material.
[0079] Wherein, the particle size of the sulfide solid electrolyte meets the following conditions: 1 μm<Dv90<1.5 μm, 0.5 μm<Dv50<1.5 μm, 0.5 μm<Dv10<1 μm.
[0080] Comparative Example 1
[0081] This comparative example provides a composite positive electrode material and a preparation method thereof, which is different from Example 1 in that: the positive electrode active material is LiFe 0.29 Mn 0.25 Nd 0.46 PO4, specifically includes the following:
[0082] The composite positive electrode material comprises a positive electrode active material and a coating material coated on the surface of the positive electrode active material; wherein the positive electrode active material is LiFe 0.29 Mn 0.25 Nd 0.46 PO4; the coating layer material is Li2S-SiS2, conductive carbon black and lithium hexafluorophosphate in a mass ratio of 1:0.2:0.4.
[0083] The method for preparing the composite positive electrode material comprises the following steps:
[0084] Step 1: weigh 10g Li2S-SiS2, 2g conductive carbon black and 4g lithium hexafluorophosphate according to the designed ratio, mix them evenly to obtain a coating mixture;
[0085] Step 2: Disperse the coating mixture in 50 mL of anhydrous methanol and add 10 g of LiFe 0.29Mn 0.25 Nd 0.28 B 0.18 PO4, ball milling and mixing at a speed of 200 rpm for 4 h, and drying to obtain a composite cathode material precursor;
[0086] Step 3: calcining the composite positive electrode material precursor at 450° C. for 5 h to obtain a composite positive electrode material.
[0087] Wherein, the positive electrode active material LiFe 0.29 Mn 0.25 Nd 0.46 The preparation method of PO4 comprises the following steps:
[0088] S1. According to the designed ratio, 1.16 g lithium oxide, 1.84 g iron oxide, 0.88 g manganese dioxide, 6.20 g neodymium oxide and 5.68 g phosphoric acid were weighed and mixed, and the mixture was put into a ball mill with a ball-to-material ratio of 30:1. The mixture was ball-milled at a speed of 450 rpm for 6 h to obtain a mixture;
[0089] S2. In an inert atmosphere, the mixture is heated to 550° C. at a heating rate of 5° C. / min, and pre-sintered for 5 hours to obtain a primary sintered product;
[0090] S3. In an inert atmosphere, the primary sintered product is heated to 850° C. at a heating rate of 5° C. / min again, calcined for 14 h, cooled, and ground to obtain a positive electrode active material.
[0091] Wherein, the particle size of the sulfide solid electrolyte meets the following conditions: 1 μm<Dv90<1.5 μm, 0.5 μm<Dv50<1.5 μm, 0.5 μm<Dv10<1 μm.
[0092] Comparative Example 2
[0093] This comparative example provides a composite positive electrode material and a preparation method thereof, which is different from Example 1 in that: the coating layer material is Li2S-SiS2 and conductive carbon black in a mass ratio of 1:0.2, specifically including the following contents:
[0094] The composite positive electrode material comprises a positive electrode active material and a coating material coated on the surface of the positive electrode active material; wherein the positive electrode active material is LiFe 0.29 Mn 0.25 Nd 0.28 B 0.18 PO4; the coating layer material is Li2S-SiS2, conductive carbon black and lithium hexafluorophosphate in a mass ratio of 1:0.2.
[0095] The method for preparing the composite positive electrode material comprises the following steps:
[0096] Step 1: weigh 10g Li2S-SiS2 and 2g conductive carbon black according to the designed ratio, mix them evenly to obtain a coating mixture;
[0097] Step 2: Disperse the coating mixture in 50 mL of anhydrous methanol and add 10 g of LiFe 0.29 Mn 0.25 Nd 0.28 B 0.18 PO4, ball milling and mixing at a speed of 200 rpm for 4 h, and drying to obtain a composite cathode material precursor;
[0098] Step 3: calcining the composite positive electrode material precursor at 450° C. for 5 h to obtain a composite positive electrode material.
[0099] Wherein, the positive electrode active material LiFe 0.29 Mn 0.25 Nd 0.28 B 0.18 The preparation method of PO4 comprises the following steps:
[0100] S1. According to the designed ratio, 1.16 g lithium oxide, 1.84 g iron oxide, 0.88 g manganese dioxide, 3.78 g neodymium oxide, 0.44 g boric acid and 5.68 g phosphoric acid were weighed and mixed, and the mixture was put into a ball mill with a ball-to-material ratio of 30:1, and the mixture was ball-milled at a speed of 450 rpm for 6 h to obtain a mixture;
[0101] S2. In an inert atmosphere, the mixture is heated to 550° C. at a heating rate of 5° C. / min, and pre-sintered for 5 hours to obtain a primary sintered product;
[0102] S3. In an inert atmosphere, the primary sintered product is heated to 850° C. at a heating rate of 5° C. / min again, calcined for 14 h, cooled, and ground to obtain a positive electrode active material.
[0103] Wherein, the particle size of the sulfide solid electrolyte meets the following conditions: 1 μm<Dv90<1.5 μm, 0.5 μm<Dv50<1.5 μm, 0.5 μm<Dv10<1 μm.
[0104] In order to further demonstrate the technical effect of the present invention, the present invention prepared a solid-state lithium battery using the composite positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-2. The specific preparation method is shown in the experimental example.
[0105] Test example
[0106] In a glove box filled with argon, the composite positive electrode material is fully dissolved in n-heptane to form a uniformly dispersed slurry, which is evenly coated on the surface of the aluminum foil and then transferred to a vacuum drying oven for complete drying. The obtained electrode sheet is rolled and then punched to obtain a positive electrode sheet. The lithium sheet is used as the negative electrode sheet, and 100 mg of sulfide Li6PS5Cl is used as the solid electrolyte. It is pressed into a sheet under a pressure of 300 MPa to obtain a solid electrolyte sheet. The positive electrode sheet, solid electrolyte sheet and negative electrode sheet are stacked and assembled in the order of stacking to form a 45mm*55mm soft-pack stacked solid-state lithium battery.
[0107] The present invention conducts the following tests on solid-state lithium batteries prepared by using the composite positive electrode materials provided in each embodiment and comparative example: the test temperatures are respectively high temperature 60°C, room temperature 25°C and low temperature -30°C.
[0108] (1) First discharge capacity, first cycle coulomb efficiency and cycle performance test: At 25°C, the solid-state battery was charged to 4.5V at a constant current of 0.1C to obtain the first charge capacity C0 of the solid-state battery, and then discharged to 2.0V at a constant current of 0.1C to obtain the first cycle discharge capacity C1 of the solid-state battery. Then, the charge and discharge cycle was repeated at a constant current of 0.1C for 500 cycles, and the discharge specific capacity C of the 500th cycle was obtained. 500 The coulombic efficiency of the first cycle of the battery = C1 / C0×100%; the capacity retention rate of the battery after 500 cycles = C 500 / C1×100%.
[0109] (2) Rate performance test: The solid-state battery is charged to 4.5V at a constant current of 0.33C, and then discharged to 2.0V at a constant current of 0.33C to obtain a discharge capacity corresponding to 0.33C; then the solid-state battery is charged to 4.5V at a constant current of 0.5C, and then discharged to 2.0V at a constant current of 0.5C to obtain a discharge capacity corresponding to 0.5C; then the solid-state battery is charged to 4.5V at a constant current of 1C, and then discharged to 2.0V at a constant current of 1C to obtain a discharge capacity corresponding to 1C.
[0110] The test results are shown in Table 1-3.
[0111] Table 1 Performance test results of various solid-state batteries at high temperature
[0112]
[0113] Table 2 Test results of solid-state battery performance at room temperature
[0114]
[0115] Table 3 Performance test results of various solid-state batteries at low temperature
[0116]
[0117] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite positive electrode material, characterized in that: The composite positive electrode material comprises a positive electrode active material and a coating material coated on the surface of the positive electrode active material; wherein the positive electrode active material is LiFe x Mn y RE z B (1-x-y-z) PO4, wherein 0.1<x≤0.3, 0.1<y<0.3, 0.1<z<0.3, 0.1<1-xyz<0.2, RE is any one of La, Ce, Nd, Y or Sm; the coating material is a mixture of a sulfide solid electrolyte, a conductive agent and a lithium salt; The coating material is a sulfide solid electrolyte, a conductive agent and a lithium salt in a mass ratio of 1:0.2:0.3-1:0.3:0.
5.
2. The composite positive electrode material according to claim 1, characterized in that: The positive electrode active material is LiFe 0.29 Mn 0.25 Nd 0.28 B 0.18 PO4、LiFe 0.3 Mn 0.26 Sm 0.25 B 0.19 PO4 or LiFe 0.25 Mn 0.27 La 0.29 B 0.19 Any of PO4.
3. The composite positive electrode material according to claim 1 or 2, characterized in that: The method for preparing the positive electrode active material comprises the following steps: S1. Weigh a lithium source, an iron source, a manganese source, an RE source, a boron source and a phosphorus source according to the designed ratio, mix them, and perform ball milling to obtain a mixture; S2. In an inert atmosphere, heating the mixture to 500° C.-600° C. for pre-sintering to obtain a primary sintered product; S3. In an inert atmosphere, the primary sintered product is heated to 800° C.-900° C. again, calcined, cooled, and ground to obtain a positive electrode active material.
4. The composite positive electrode material according to claim 3, characterized in that: In S1, the ball-to-material ratio of the ball mill is 25:1-35:1, the rotation speed of the ball mill is 400rpm-500rpm, and the ball milling time is 3h-8h; and / or In S2, the temperature is raised to 500°C-600°C by programmed heating, with a heating rate of 2°C / min-10°C / min; and / or In S2, the pre-sintering time is 4h-6h.
5. The composite positive electrode material according to claim 3, characterized in that: In S3, the temperature is raised to 800°C-900°C by programmed heating, with a heating rate of 5°C / min-10°C / min; and / or In S3, the calcination time is 12h-16h.
6. The composite positive electrode material according to claim 1, characterized in that: The coating thickness of the coating material is 3nm-10nm.
7. The composite positive electrode material according to claim 1, characterized in that: The sulfide solid electrolyte is Li2S-SiS2, Li2S-B2S3, Li6PS5Cl, Li7P3S 11 , LiSiPSCl, LiSiPSBr or LiSiPSI; and / or The particle size of the sulfide solid electrolyte meets the following conditions: 1 μm<Dv90<1.5 μm, 0.5 μm<Dv50<1.5 μm, 0.5 μm<Dv10<1 μm; and / or The conductive agent is conductive carbon black; and / or The lithium salt is any one or two of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(difluorosulfonyl)imide, lithium bis(oxalatoborate) or lithium difluorooxalatoborate.
8. The method for preparing a composite positive electrode material according to any one of claims 1 to 7, characterized in that: The steps include: Step 1: weighing a sulfide solid electrolyte, a conductive agent and a lithium salt according to the designed ratio, and mixing them evenly to obtain a coating mixture; Step 2: dispersing the coating mixture in an alcohol solvent, adding a positive electrode active material, ball milling and mixing, and drying to obtain a composite positive electrode material precursor; Step 3: calcining the composite positive electrode material precursor at 400° C.-500° C. to obtain a composite positive electrode material.
9. The method for preparing a composite positive electrode material according to claim 8, characterized in that: In step 2, the alcohol solvent is anhydrous methanol or anhydrous ethanol; and / or In step 2, the mass volume ratio of the coating mixture to the alcohol solvent is 1g:3mL-1g:5mL; and / or In step 2, the mass ratio of the coating mixture to the positive electrode active material is 1.2:1-2.0:1; and / or In step 2, the rotation speed of the ball mill is 200 rpm-300 rpm, and the time of the ball mill is 3 h-4 h; and / or In step three, the calcination time is 4h-6h.
10. Use of the composite positive electrode material according to any one of claims 1 to 7 or the composite positive electrode material prepared by the method for preparing the composite positive electrode material according to claim 8 or 9 in a solid-state lithium battery.
Citation Information
Patent Citations
Lithium-ion-battery cathode active material, preparation method thereof, cathode and battery
CN104124451A
Lithium battery core-shell positive electrode material, lithium battery containing lithium battery core-shell positive electrode material and preparation method of lithium battery
CN113871588A
Lithium manganese iron phosphate positive electrode material, preparation method thereof and battery
CN115724418A
Lithium manganese iron phosphate positive electrode material, preparation method and application thereof
CN115832257A
Doped lithium iron manganese phosphate positive electrode material, preparation method thereof, positive electrode plate containing doped lithium iron manganese phosphate positive electrode material, and lithium ion battery containing doped lithium iron manganese phosphate positive electrode material
CN116741987A